Translation strategies of metaphor in The Ballad of Never After novel by Stephanie Garber - Darmapratiwi, Kadek; Pratiwi, Desak Putu Eka (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Metaphor is a figurative language often found in literary works, especially novels. It contains unique cultural elements, which makes metaphor hard to understand and translate. This study examines the strategy of translating metaphors in The Ballad of Never After novel from English into Indonesian. Data were analyzed using the qualitative descriptive method completed with the theory by Newmark (1988) regarding translation strategies of metaphor. This study revealed that from the 96 data obtained, seven translation strategies of metaphor were used by translators to convey the meaning of the metaphors in the novel from English to Indonesian and reproducing the Same Image in the Target Language is the most frequently used strategy. In contrast, the least used strategy is Changing the Metaphor by Simile Combined with Sense and Deleting. It indicates that English and Indonesian share many metaphorical images with similar meanings. It causes translators being more flexible in reproducing metaphors in the target language, considering cultural similarities and the circumstances in which metaphors are expressed.